Multicenter Study on Transarterial Chemoembolization Combined with Radiofrequency Ablation for Early-Stage Hepatocellular Carcinoma: Primary versus Recurrent HCC - Chen YT; Chen BWT; Xu JM; You XC; Tang Y; Wu SJ; Fang ZT (Journal of Hepatocellular Carcinoma)
Yu-Tang Chen,1,2,* Bo-Wen-Tao Chen,3,* Jun-Ming Xu,1,4,* Xiao-Cui You,1 Yi Tang,3 Shao-Jie Wu,3 Zhu-Ting Fang1,3 1Department of Oncology and Vascular Interventional Therapy, Clinical Oncology School of Fujian Medical University, Fujian Cancer Hospital (Fujian Branch of Fudan University Shanghai Cancer Center), Fuzhou, People’s Republic of China; 2Department of Interventional Radiology, Sanming Second Hospital, Sanming, People’s Republic of China; 3Department of Interventional Radiology, Fujian Provincial Hospital, Shengli Clinical Medical, College of Fujian Medical University, Fuzhou University Affiliated Provincial Hospital, Fuzhou, People’s Republic of China; 4Department of Interventional Radiology, Zhangzhou Affiliated Hospital of Fujian Medical University, Zhangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhu-Ting Fang, Email ztfang@fjzlhospital.comPurpose: To evaluate the efficacy of transarterial chemoembolization (TACE) combined with radiofrequency ablation (RFA) for both primary and recurrent early-stage hepatocellular carcinoma (HCC) and to analyze the significant prognostic factors.Patients and Methods: Data from patients with early-stage primary or recurrent HCC who underwent TACE plus RFA between August 2019 and May 2024 were collected from three major general hospitals. 158 patients were divided into a primary group and a recurrent group on the basis of their baseline characteristics. Compared the objective response rate (ORR), 1-, 3-, and 5-year progression-free survival (PFS) rates, 1-, 3-, and 5-year overall survival (OS) rates, and complication rate between the two groups. Multivariate analyses were used to evaluate the factors influencing PFS and OS.Results: One hundred fifty-eight patients were enrolled. The ORRs of the primary and recurrent groups were 98.2% and 95.1%, respectively, with no statistically significant difference (χ2= 2.032, &Rgr; = 0.362). The primary group having a significantly longer PFS time than the recurrent group (&Rgr; < 0.001). However, there was no significant difference in the 1-, 3-, and 5-year OS rates between the two groups (&Rgr; = 0.218). Multivariate analysis revealed that primary or recurrent HCC and the Child‒Pugh score were significant prognostic factors for PFS, whereas the serum albumin level was a significant prognostic factor for OS.Conclusion: TACE plus RFA has similar clinical efficacy and safety for both primary and recurrent early HCC. Compared with patients with primary HCC, those with recurrent disease had significantly shorter PFS times.Keywords: hepatocellular carcinoma, radiofrequency ablation, transarterial chemoembolization